Diversity of dinoflagellate cysts isolated from estuarine sediments of the Bengawan Solo and Brantas rivers, Indonesia - SAPTO ANDRIYONO; NITA RUKMINASARI; ANDI ALIAH HIDAYANI; INDRA JUNAIDI ZAKARIA; MD. JOBAIDUL ALAM; HYUN-WOO KIM KIM (Society for Indonesian Biodiversity, 2023)
Abstract. Andriyono S, Rukminasari N, Hidayani AA, Zakaria IJ, Alam MDJ, Kim HW. 2023. Diversity of dinoflagellate cysts isolated from estuarine sediments of the Bengawan Solo and Brantas rivers, Indonesia. Biodiversitas 24: 1083-1091. Dinoflagellates are a major part of the phytoplankton and are commonly found in freshwater, brackish, and marine habitats and are major components that play an important role in marine ecosystems. Dinoflagellate cysts (dinocysts) are produced by dinoflagellates in an unfavourable environment and can be preserved well in sediments for long periods. More than 200 dinoflagellate species have been observed to produce resting cysts. That cyst is associated with the maintenance, discontinuation, and repetition of annual blooms. This study identified dinoflagellate cysts based on the morphological characteristics collected from the estuaries of the Brantas and Bengawan Solo rivers. Analysis of cyst diversity in the two regions shows that the Bengawan Solo River mouth has a higher Shannon-Wiener index compared to the Brantas river mouth. The type of dinoflagellate cyst that dominates at the mouth of the Bengawan Solo River is Protoperidinium obtusum, while that at the mouth of the Brantas River is Polykrikos schwartzii. Shade graph analysis shows a number of species to be found only in the estuary of the Bengawan Solo River, namely Zygabikodinium lenticulatum, Polykrikos kofoidii, Protoperidinium pentagonum, Gymnodinium catenatum, and Votadinium sp. Based on the results of this study, it is necessary to carry out DNA characteristic tests of isolated and cultured species to document genetic information. In addition, this information is very important in the management of coastal areas around the estuaries of the Bengawan Solo and Brantas rivers to prevent dinoflagellate population explosions that may have negative impacts on various sectors.